(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to identify the impact of the program Algebrator in the acquisition of mathematical concepts among students of the second intermediate grade, and to achieve the goal of the research, the experimental method with two groups (experimental and control) with a post-test was adopted, as the number of the research sample reached (54) students from the class. The second average was distributed into two groups, one of them was an experimental group whose members were (28) students who were studied according to the Algebrator program, and the other was a control group whose members numbered (26) students who were studied according to the usual method, and the two groups were equalized with a number of variables. A multiple-choice test for acquiring mathematical concepts was prepared consisting of (30) test items, and the appropriate statistical analyzes were conducted for the research tool while ensuring its psychometric properties. The results showed the superiority of the experimental group that was taught using the Algebrator program over the control group in acquiring mathematical concepts. In light of the research results, it was recommended to take advantage of the Algebrator program in teaching and learning mathematics, training educational staff on how to use it, and paying attention to computer-based teaching methods that enhance students’ self-confidence. He also suggested conducting a study similar to the current research on other variables such as mathematical thinking and solving mathematical problems.